Analisis Perbandingan Sistem Persinyalan Konvensional Dengan CBTC Terhadap Headway Kereta Api - Agra Aptana; Muhammad Fahmi Arsyad; Ponco Hadi Prasetyo (Fakultas Teknik Transportasi dan Logistik Trisakti, 2023)
KRL Commuter Line and MRT Jakarta, serving urban population mobility with high transport capacity. The development of urban rail signaling, making the choice of signaling system application to headway be competitive. However, it is necessary to choose the right one, so this research is carried out, with the aim of knowing the effect of the signaling system on headway urban railways, by comparing conventional and CBTC signaling systems. This research method is quantitative and qualitative, using primary data from observation at MRT Jakarta, Gapeka KRLCommuter Line and Time Table MRT Jakarta, interviews with experts and passenger through techniques purposive sampling and based analysis coding. The results of research that CBTC uses moving block, make headway more stable. Headway Jakarta MRT 3 minutes, with 99.98% time liness and better than KRL Commuter Line. Factor affecting headway urban trains, namely crossing gates, number of facilities, length of traffic, number of stopping stations, dwelling time, signaling systems, and personnel.